Mangrove Tourism Development Strategy for the Prosperous Village on Baai Island, Bengkulu City - Anggie Aditya Heriyanto; Sri Handayani; Mimi Kurnia Nengsih (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2021)
The aim of being able to see what development strategies are suitable for mangrove tourism in Kampung Sejahtera on Baai Island, Bengkulu City. The research objective was to see the strategy for developing mangrove tourism in Kampung Sejahtera on Baai Island, Bengkulu City with a SWOT analysis. The data collection used was a questionnaire method with a list of questions to the respondents. The analysis method used is a SWOT analysis to see internal factors and external factors, which will then be entered into the SWOT matrix. The research results obtained from the analysis of internal factors and external factors. The result of the internal factor is a strength (strength) of 2.75 while the weakness (weakness) is 1.46, so the value of the internal factor is 2.75-1.46 = 1.29 while from the external factor the opportunity (opportunity) is 2 , 52 and for the threat (threat) is 1.58, the value of the external factor is 2.52-1.58 = 0.94. Based on the analysis diagram, the SWOT strategy is in the Cell (quadrant) I position. This shows that the SO strategy in the SWOT matrix is an aggressive strategy. This strategy explains that Kampung Sejahtera mangrove tourism can take advantage of the surrounding environment. The environment around mangrove tourism is still natural so that it is very likely for the community to add stages such as trading, opening food stalls, and lodging businesses around the mangrove tourism of Kampung Sejahtera on Baai Island, Bengkulu City, and Utilizing mangrove forests so as not to abrasion around mangrove tourism Kampung Sejahtera on Baai Island, Bengkulu City, which makes the tourist area safe and tourists who visit are comfortable and not worried about abrasion